Determination of [11C]PBR28 Binding Potential in vivo: A First Human TSPO Blocking Study. Issue 6 (June 2014) - Owen, David R; Guo, Qi; Kalk, Nicola J; Colasanti, Alessandro; Kalogiannopoulou, Dimitra; Dimber, Rahul; Lewis, Yvonne L; Libri, Vincenzo; Barletta, Julien; Ramada-Magalhaes, Joaquim; Kamalakaran, Aruloly; Nutt, David J; et al.
Positron emission tomography (PET) targeting the 18 kDa translocator protein (TSPO) is used to quantify neuroinflammation. Translocator protein is expressed throughout the brain, and therefore a classical reference region approach cannot be used to estimate binding potential ( BP ND ). Here, we used blockade of the TSPO radioligand [ 11 C]PBR28 with the TSPO ligand XBD173, to determine the non-displaceable volume of distribution ( V ND ), and hence estimate the BP ND . A total of 26 healthy volunteers, 16 high-affinity binders (HABs) and 10 mixed affinity binders (MABs) underwent a [ 11 C]PBR28 PET scan with arterial sampling. Six of the HABs received oral XBD173 (10 to 90 mg), 2 hours before a repeat scan. In XBD173-dosed subjects, V ND was estimated via the occupancy plot. Values of BP ND for all subjects were calculated using this V ND estimate. Total volume of distribution ( V T ) of MABs (2.94 ± 0.31) was lower than V T of HABs (4.33 ± 0.29) ( P <0.005). There was dose-dependent occupancy of TSPO by XBD173 (ED50 = 0.34 ± 0.13 mg/kg). The occupancy plot provided a V ND estimate of 1.98 (1.69, 2.26). Based on these V ND estimates, BP ND for HABs is approximately twice that of MABs, consistent with predictions from in vitro data. Our estimates of [ 11 C]PBR28 V ND and hence BP ND in the healthy human brain are consistent with in vitro predictions. XBD173 blockade provides a practical means of estimating V ND for TSPO targeting radioligands.